2019
DOI: 10.14744/nci.2019.23427
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Dysplasia Frequency and Risk Factors in Very Low Birth Weight İnfants: a 3-Year Retrospective Study

Abstract: B ronchopulmonary dysplasia (BPD) is a chronic lung disease requiring long-term oxygen support with ≥21% concentration with a variety of modalities in premature infants. Until the 2000s, the diagnosis was made based on whether oxygen requirements continued up to the postnatal 28 th day. However, after this date, diagnosis began to be made based on the severity of the disease as mild, moderate and severe according to gestational week (GW) [1, 2]. Low birth weight (WB) and GW are usual risk factors for BPD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 54 publications
(44 reference statements)
9
14
0
Order By: Relevance
“…The risk factors in these OD preterms cohort study are similar to that found in the literature, with the predominance of male patients and a history of maternal infection in more than 28% of cases, followed by toxemia (22%) and premature rupture of membranes (18.4%) 14–17 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The risk factors in these OD preterms cohort study are similar to that found in the literature, with the predominance of male patients and a history of maternal infection in more than 28% of cases, followed by toxemia (22%) and premature rupture of membranes (18.4%) 14–17 …”
Section: Discussionsupporting
confidence: 80%
“…The risk factors in these OD preterms cohort study are similar to that found in the literature, with the predominance of male patients and a history of maternal infection in more than 28% of cases, followed by toxemia (22%) and premature rupture of membranes (18.4%). [14][15][16][17] Regarding postnatal history, almost half of our patients received invasive ventilation (51.4%), with a median duration of 2 days. This highlights the need to avoid this type of ventilatory support as much as possible, favoring strategies such as CPAP and/or nasal ventilation from the delivery room.…”
Section: Discussionmentioning
confidence: 99%
“…The history of the OD preterm cohort in this study is similar to that found in the literature, with predominance of male patients and a history of maternal infection in more than 50% of the cases, followed by toxemia (21%) and premature rupture of membranes (6.7%) [14][15][16][17] .…”
Section: Discussionsupporting
confidence: 83%
“…Infants with immature lung development are prone to BPD (24)(25)(26). The results of this study showed that infants with a history of neonatal asphyxia and NRDS were at higher risk of developing BPD, consistent with the results of several previous studies.…”
Section: Analysis Of Risk Factors For Bpd In Vlbwismentioning
confidence: 99%